Dampak Media Sosial Terhadap Moral Siswa di SD Negeri 04 Payaraman Kabupaten Ogan Ilir - Dwi Amalia; Tutut Handayani; Fuaddilah Ali Sofyan; Sunardi Sunardi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine the impact of social media on student morale. The method used in this research is a qualitative method. The subjects in this study were homeroom teachers of class V and students of class V. The approach used was a qualitative descriptive approach with data collection techniques using observation, interview and documentation techniques. The results of the study are that at the State School Zero Empat Payaraman the use of social media is not exempt, because the impact of the use of social media in the school environment greatly affects all aspects, both aspects of achievement and enthusiasm for learning. With the use of social media in the school environment, students are only busy or focused on smartphones. The use of social media, of course, has a lot of impact on its users, both positive and negative impacts. There are many positive impacts of social media when it comes to children's education, one of which is that children can learn how to adapt, socialize with the public and manage friendship networks in learning activities.